Nature and city: the scenarios of Persiles - Arellano, Ignacio (2019)
The work presents an approach to the work of Miguel de Cervantes Saavedra Los trabajos de Persiles y Seguismunda (1617), known as El Persiles, from different scenarios that have to do with the topic of nature: the caves, the sea, the islands locus amoenus, and some aspects that have to do with geography.